2024
DOI: 10.1029/2023je008187
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology and Stratigraphy of the Shenandoah Formation, Western Fan, Jezero Crater, Mars

K. M. Stack,
L. R. W. Ives,
S. Gupta
et al.

Abstract: Sedimentary fans are key targets of exploration on Mars because they record the history of surface aqueous activity and habitability. The sedimentary fan extending from the Neretva Vallis breach of Jezero crater's western rim is one of the Mars 2020 Perseverance rover's main exploration targets. Perseverance spent ∼250 sols exploring and collecting seven rock cores from the lower ∼25 m of sedimentary rock exposed within the fan's eastern scarp, a sequence informally named the “Shenandoah” formation. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 141 publications
0
20
0
Order By: Relevance
“…Surface rocks analyzed by the Perseverance rover at JWF, indicate distinct formation compared to on the Crater Floor. Whereas the latter was mainly concluded to have magmatic origin (Farley et al, 2022), JWF is found to represent a sedimentary fan deposit (Stack et al, 2024). The difference in radar propagation velocities between the Crater Floor and JWF, is consistent with change from magmatic lithologies to sedimentary.…”
Section: Implications For Regolith Compositionmentioning
confidence: 66%
“…Surface rocks analyzed by the Perseverance rover at JWF, indicate distinct formation compared to on the Crater Floor. Whereas the latter was mainly concluded to have magmatic origin (Farley et al, 2022), JWF is found to represent a sedimentary fan deposit (Stack et al, 2024). The difference in radar propagation velocities between the Crater Floor and JWF, is consistent with change from magmatic lithologies to sedimentary.…”
Section: Implications For Regolith Compositionmentioning
confidence: 66%
“…These results indicate that the mineralogy of the fan front and the upper fan are distinct: the fan front is dominated by sulfates while the upper fan has almost two times more carbonate detections than sulfate detections. PIXL analyses of elemental composition report ∼20 wt.% SO 3 in the sulfatedominated targets Berry Hollow and Uganik Island in the fan front, which is ∼25× greater than in the sulfatecontaining crater floor target Dourbes (Liu et al, 2022;Stack et al, 2024). SuperCam observations also report the upper fan to be dominated by carbonates with no sulfate detections (Royer, Wiens, et al, 2023).…”
Section: Sulfate Mineralogymentioning
confidence: 95%
“…We conduct a statistical analysis of the deep-UV Raman spectra of all stratigraphically in-place rock targets measured by SHERLOC at the Séítah and Máaz formations of the crater floor, the fan front (informally named the Shenandoah formation, Stack et al, 2024), and the upper fan deposits (informally named the Tenby formation, e.g., Siebach et al, 2023) of the sedimentary western fan. We first analyze Raman spectral features in SHERLOC scans at 100 μm/point spatial scale over 800-1,200 cm 1 to identify the alteration minerals present.…”
Section: Introductionmentioning
confidence: 99%
“…The base of the Hawksbill Gap stratigraphy corresponds to the Devils Tanyard member and overlying Hughes River Gap strata (Figure 1), which consist of planar laminated sandstones of variable exposure. Here, the outcrops share morphological and spectral features with the Knife Creek member (located right above Amalik) and hence have been interpreted as its lateral equivalent in the Cape Nukshak section (Dehouck et al, 2023;Stack et al, 2024). Abrasion of a Devils Tanyard rock (target Rose River Falls) shows the strongest oxidation of Fe features: the rock is redder than the other abraded members, has narrower reflectance peaks in the visible, and deeper 0.53 and 0.86 μm absorptions, indicative of fine-grained crystalline hematite (Figures 3 and 5).…”
Section: Devils Tanyard/hughes River Gap/knife Creek Membermentioning
confidence: 99%
“…We compare their spectral signatures to those of igneous rocks present on the crater floor (below the sedimentary units) as well as similar data from prior Mars landing sites to understand the changes in weathering and redox state. This work is conducted in parallel with others that define the fan stratigraphy (Stack et al, 2024), present the overviews of SuperCam (Dehouck et al, 2023) and Mastcam-Z (Núñez et al, 2023) results from Jezero's western fan, or use other rover instruments to interrogate composition (e.g., Hurowitz et al, 2023;Phua et al, 2024).…”
Section: The Mars 2020 Missionmentioning
confidence: 99%